An anti-aging composition and its preparation method and skin care application
By developing an anti-aging composition containing anti-wrinkle compositions, soy lecithin and other ingredients, and using high-speed shearing and high-pressure homogenization processes to prepare nano-alcohol bodies, the problems of light instability, activity attenuation and skin irritation in existing anti-aging skin care products have been solved, and the anti-aging effect of good stability and good absorption is achieved.
Patent Information
- Application Number
- CN202111466108.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-12-03
AI Technical Summary
Among the existing anti-aging skin care products, retinol and its derivatives have problems with photoinstability, activity attenuation and skin irritation, and traditional liposomes have poor stability and poor absorption.
An anti-aging composition is developed, including anti-wrinkle composition, soy lecithin, glycerol, caprylic/capric triglyceride, propylene glycol, polysorbate-80, palmitoyl pentapeptide-4, and Dendrobium officinale stem extract, and deformable flexible nanoalcohol bodies are prepared by high-speed shearing and high-pressure homogenization and other processes.
The composition has good stability and good transdermal absorption, which can repair the skin tissue morphology, accelerate the renewal of elastic fibers, promote the generation of collagen fibers, and achieve the effect of anti-aging and firming skin.
Smart Images

Figure CN116236431B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of daily chemicals, and in particular to an anti-aging composition, a preparation method thereof and skin care application thereof. Background Art
[0002] Skin aging is mainly due to two reasons, one is endogenous aging and the other is exogenous aging. Endogenous aging mainly refers to the aging characteristics of the skin with age: more wrinkles, sagging and yellowing of the skin, reduced luster, luster and smoothness, coarsening of the texture, and more spots; exogenous aging mainly refers to the accelerated damage to skin cells and the acceleration of natural aging due to staying up late, work pressure, life anxiety, ultraviolet damage, etc. In addition, there is also a kind of expression lines caused by personal expression habits, which cannot be avoided by self-consciousness. Because the skin is repeatedly stretched and relaxed by the muscles, the collagen will be rearranged, and wrinkles will eventually form over time. With the rapid development of the economy and the improvement of people's living standards, consumers are pursuing more and more anti-aging cosmetics, especially functional ingredients, care effects and safety. At present, there are many kinds of "anti-aging" raw materials on the market, but there are generally problems such as insufficient efficacy, single effect, poor absorption, and unstable functional ingredients. For example, the commonly used raw material "retinol" in anti-aging skin care products and its many derivatives are called the "retinoids" family, including: retinal, retinoic acid (i.e. "retinoic acid" or "retinoic acid"), retinyl esters (such as retinol palmitate, retinol acetate, retinol propionate, retinol retinoic acid ester, etc.), β-carotene, etc., which are often used in anti-aging products such as creams, essences and eye creams. However, there are some problems in the application of retinol: ① Photoinstability: Since the tetraene side chain of retinol is easy to accept the energy of light waves, it is easy to change its structure under ultraviolet irradiation and lose its activity; ② Activity attenuation problem: Experimental studies have shown that at room temperature, retinol, retinal, and retinol lipid standard solutions have different degrees of activity attenuation, among which retinol has the most serious attenuation; ③ Irritation to the skin: People with different skin types show different tolerance when using it, and may experience discomfort such as erythema, peeling, and pain. Literature (Fu PP, Cheng SH, Coop L, et al. Photoreaction, phototoxicity, and photocarcinogenicity of retinoids [J]. Journal of Environmental Science and Health Part C: Environmental Carcinogenesis & Ecotoxicology Reviews, 2003, 21 (2): 165-197.) found that compared with retinol, retinyl palmitate is less stable under UV light, and UVB has a stronger photodegradation effect on retinoids, making it photosensitizing and phototoxic. At the same time, due to the safety risks of retinoids, their use in skin care products is limited.
[0003] Traditional liposomes are hollow liposomes made of lecithin and ceramide, with a bilayer structure. The main raw materials are phospholipids and cholesterol. The hydrophilic head of the phospholipid molecule extends into the water, and the hydrophobic tail extends into the air. Cholesterol is embedded between the phospholipid molecules, which has the function of regulating membrane fluidity and has an excellent moisturizing effect on the skin. In particular, liposomes coated with moisturizing substances such as hyaluronic acid and polyglucosidase are better moisturizing substances. However, traditional liposomes have problems such as poor stability, low encapsulation rate of fat-soluble active substances, and low transdermal penetration rate.
[0004] Based on this, it is of great practical significance to develop an anti-aging skin care product raw material with good stability, good transdermal absorption, and the effect of repairing skin tissue damage. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an anti-aging composition, a preparation method thereof and skin care application. The anti-aging composition has good stability and good transdermal absorption, can repair skin tissue morphology, accelerate elastic fiber renewal, promote collagen fiber production, and achieve anti-aging and skin firming effects.
[0006] To this end, the technical solutions provided by this application are as follows:
[0007] The first aspect of the present invention provides an anti-aging composition.
[0008] According to the present invention, the anti-aging composition comprises an anti-wrinkle composition, soybean lecithin, glycerin, caprylic / capric triglyceride, propylene glycol, polysorbate-80, palmitoyl pentapeptide-4, Dendrobium officinale stem extract, and water.
[0009] In the present invention, the Dendrobium officinale stem extract is a water extract. In some embodiments, the preparation method of the Dendrobium officinale stem extract comprises: extracting the Dendrobium officinale stem by mixing with water, filtering, membrane separation, drying and crushing, and sterilizing.
[0010] In the present invention, the CAS number of caprylic acid / capric acid triglyceride is 73398-61-5, and the CAS number of arginine / lysine polypeptide is 936616-33-0.
[0011] According to the present invention, the anti-aging composition includes, by weight percentage, 30.00wt%-70.00wt% of an anti-wrinkle composition, 0.50wt%-2.50wt% of soy lecithin, 2.50wt%-12.50wt% of glycerol, 0.25wt%-1.25wt% of caprylic / capric triglyceride, 15.00wt%-35.00wt% of propylene glycol, 0.25wt%-1.25wt% of polysorbate-80, 0.01wt%-0.03wt% of palmitoyl pentapeptide-4, 0.10wt%-0.20wt% of Dendrobium officinale stem extract, and water To100.
[0012] According to the present invention, the amount of the anti-wrinkle composition added to the anti-aging composition is 30.00wt%-70.00wt%, for example, 30.00wt%, 40.00wt%, 50.00wt%, 60.00wt%, 70.00wt%, and points between the above values.
[0013] According to the present invention, the amount of soybean lecithin added to the anti-aging composition is 0.50wt%-2.50wt% by weight, for example, it can be 0.50wt%, 1.00wt%, 1.50wt%, 2.00wt%, 2.50wt%, and points between the above values.
[0014] According to the present invention, the amount of glycerol added to the anti-aging composition is 2.50wt%-12.50wt%, for example, 2.50wt%, 5.00wt%, 7.50wt%, 10.00wt%, 12.50wt%, and points between the above values.
[0015] According to the present invention, the amount of caprylic / capric triglyceride added to the anti-aging composition is 0.25wt%-1.25wt%, for example, it can be 0.25wt%, 0.50wt%, 0.75wt%, 1.00wt%, 1.25wt%, and points between the above values.
[0016] According to the present invention, the amount of propylene glycol added to the anti-aging composition is 15.00wt%-35.00wt%, for example, 15.00wt%, 20.00wt%, 25.00wt%, 30.00wt%, 35.00wt%, and points between the above values.
[0017] According to the present invention, the amount of polysorbate-80 added to the anti-aging composition is 0.25wt%-1.25wt%, for example, 0.25wt%, 0.50wt%, 0.75wt%, 1.00wt%, 1.25wt%, and points between the above values.
[0018] According to the present invention, the anti-aging composition comprises, by weight percentage, 40.00wt%-60.00wt% of an anti-wrinkle composition, 0.75wt%-1.25wt% of soy lecithin, 2.50wt%-12.50wt% of glycerol, 0.50wt%-1.00wt% of caprylic / capric triglyceride, 20.00wt%-30.00wt% of propylene glycol, and 0.50wt%-1.00wt% of polysorbate-80.
[0019] According to the present invention, the anti-wrinkle composition comprises 0.001 wt%-0.005 wt% of arginine / lysine polypeptide and water To100, based on the weight of the anti-wrinkle composition.
[0020] According to the present invention, based on the weight of the anti-wrinkle composition, the amount of arginine / lysine polypeptide added in the anti-wrinkle composition is 0.001wt%-0.005wt%, for example, it can be 0.001wt%, 0.002wt%, 0.003wt%, 0.004wt%, 0.005wt%, and points between the above values.
[0021] According to the present invention, the amount of palmitoyl pentapeptide-4 added to the anti-aging composition is 0.01wt%-0.03wt%, for example, 0.01wt%, 0.02wt%, 0.03wt%, and points between the above values.
[0022] According to the present invention, the anti-aging composition is prepared by a preparation method comprising the following steps:
[0023] 1) preparing an oil phase and an aqueous phase, wherein the oil phase comprises soybean lecithin, glycerol, caprylic / capric triglyceride, propylene glycol and palmitoyl pentapeptide-4; and the aqueous phase comprises polysorbate-80, an anti-wrinkle composition and a Dendrobium officinale stem extract;
[0024] 2) adding the oil phase to the water phase for hydration reaction to obtain a water-oil phase mixture;
[0025] 3) subjecting the water-oil phase mixture to high-speed shearing to obtain a crude alcohol body;
[0026] 4) The crude alcoholate is subjected to high pressure homogenization to obtain the alcoholate.
[0027] According to some specific embodiments of the present invention, the method for preparing the oil phase in step 1) comprises weighing soy lecithin, glycerol, caprylic / capric triglyceride and propylene glycol, dissolving them, adding palmitoyl pentapeptide-4, dissolving them, and obtaining the oil phase.
[0028] According to some specific embodiments of the present invention, the method for preparing the aqueous phase in step 1) comprises weighing polysorbate 80, the anti-wrinkle composition and the Dendrobium officinale stem extract and dissolving them in water to obtain the aqueous phase.
[0029] According to some specific embodiments of the present invention, the hydration reaction time in step 2) is 10-30 min, for example, it can be 10 min, 11 min, 13 min, 15 min, 20 min, 25 min, 30 min, and points between the above values.
[0030] According to some specific embodiments of the present invention, in step 3), the high-speed shearing speed is 6000-10000 rpm, for example, it can be 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, and points between the above values.
[0031] According to some specific embodiments of the present invention, in step 3), the high-speed shearing time is 1-5 min, for example, 1 min, 2 min, 3 min, 4 min, or 5 min.
[0032] According to some specific embodiments of the present invention, the high-pressure homogenization pressure in step 4) is 600-1000 bar, for example, it can be 600 bar, 700 bar, 800 bar, 900 bar, or 1000 bar.
[0033] According to some specific embodiments of the present invention, the number of high pressure homogenization in step 4) is 3-7 times, for example, 3 times, 4 times, 5 times, 6 times, or 7 times.
[0034] According to some specific embodiments of the present invention, the method for preparing the oil phase in step 1) includes: weighing soy lecithin, glycerol, caprylic / capric triglyceride and propylene glycol, and dissolving them, for example, at 50560°C and 5005600 rpm / min with magnetic stirring, and after the soy lecithin is fully dissolved, stopping heating, adding palmitoyl pentapeptide-4, and dissolving to obtain the oil phase.
[0035] According to some specific embodiments of the present invention, the method for preparing the aqueous phase in step 1) comprises: weighing 0.25wt%-1.25wt% of polysorbate-80, 30.00wt%-70.00wt% of the anti-wrinkle composition and 0.10wt%-0.20wt% of the Dendrobium officinale stem extract and dissolving them in water, especially ultrasonically dissolving them into a homogeneous system to obtain an aqueous phase.
[0036] The second aspect of the present invention provides a method for preparing the anti-aging composition of the first aspect of the present invention.
[0037] According to the present invention, the preparation method comprises the following steps:
[0038] 1) Weighing 0.50wt%-2.50wt% of soybean lecithin, 2.50wt%-12.50wt% of glycerol, 0.25wt%-1.25wt% of caprylic / capric triglyceride and 15.00wt%-35.00wt% of propylene glycol, dissolving them, adding 0.01wt%-0.03wt% of palmitoyl pentapeptide-4, dissolving them, and obtaining an oil phase; weighing 0.25wt%-1.25wt% of polysorbate-80, 30.00wt%-70.00wt% of an anti-wrinkle composition and 0.10wt%-0.20wt% of a stem extract of Dendrobium officinale, dissolving them in water, and dissolving them to obtain an aqueous phase;
[0039] 2) Add the oil phase to the water phase for hydration reaction for 10-30 minutes to obtain a water-oil phase mixture;
[0040] 3) High-speed shearing the water-oil mixture at 6000-10000 rpm for 1-5 min to obtain a crude alcohol body;
[0041] 4) The crude alcoholate is homogenized at a pressure of 600-1000 bar for 3-7 times to obtain an alcoholate.
[0042] According to some specific embodiments of the present invention, the hydration reaction time in step 2) is 10-30 min, for example, it can be 10 min, 11 min, 13 min, 15 min, 20 min, 25 min, 30 min, and points between the above values.
[0043] According to some specific embodiments of the present invention, in step 3), the high-speed shearing speed is 6000-10000 rpm, for example, it can be 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, and points between the above values.
[0044] According to some specific embodiments of the present invention, in step 3), the high-speed shearing time is 1-5 min, for example, 1 min, 2 min, 3 min, 4 min, or 5 min.
[0045] According to some specific embodiments of the present invention, the high-pressure homogenization pressure in step 4) is 600-1000 bar, for example, it can be 600 bar, 700 bar, 800 bar, 900 bar, or 1000 bar.
[0046] According to some specific embodiments of the present invention, the number of high pressure homogenization in step 4) is 3-7 times, for example, 3 times, 4 times, 5 times, 6 times, or 7 times.
[0047] According to some specific embodiments of the present invention, the method for preparing the oil phase in step 1) comprises: weighing 0.50wt%-2.50wt% soybean lecithin, 2.5wt%-12.5wt% glycerol, 0.25wt%-1.25wt% caprylic acid / capric acid triglyceride and 15.00wt%-35.00wt% propylene glycol, and dissolving them, for example, at 50560°C and 5005600rpm / min with magnetic stirring, and after the soybean lecithin is fully dissolved, stopping heating, adding 0.01wt%-0.03wt% palmitoyl pentapeptide-4, and dissolving to obtain the oil phase.
[0048] According to some specific embodiments of the present invention, the method for preparing the aqueous phase in step 1) comprises: weighing 0.25wt%-1.25wt% of polysorbate-80, 30.00wt%-70.00wt% of the anti-wrinkle composition and 0.10wt%-0.20wt% of the Dendrobium officinale stem extract and dissolving them in water, especially ultrasonically dissolving them into a homogeneous system to obtain an aqueous phase.
[0049] In the present invention, the preparation method of the Dendrobium officinale stem extract comprises: extracting by mixing the Dendrobium officinale stem with water, filtering, membrane separation, drying, crushing and sterilizing.
[0050] In the present invention, the CAS number of caprylic acid / capric acid triglyceride is 73398-61-5, and the CAS number of the arginine / lysine polypeptide is 936616-33-0.
[0051] Application of the anti-aging composition described in the first aspect of the present invention and / or the prepared anti-aging composition described in the second aspect of the present invention in the field of cosmetics and / or skin care products.
[0052] According to the present invention, the anti-aging composition is used in cosmetics and / or skin care products with the effect of repairing skin tissue morphology.
[0053] According to the present invention, the anti-aging composition is used in cosmetics and / or skin care products for accelerating the renewal of collagen fibers.
[0054] According to the present invention, the anti-aging composition is used in cosmetics and / or skin care products for promoting the generation of elastic fibers.
[0055] According to the present invention, the anti-aging composition is used in cosmetics and / or skin care products with anti-aging effects.
[0056] According to the present invention, the anti-aging composition is used in cosmetics and / or skin care products with skin tightening effect.
[0057] Beneficial effects of the present invention:
[0058] The anti-aging composition of the present invention comprises soybean lecithin, palmitoyl pentapeptide-4, arginine / lysine polypeptide, Dendrobium officinale stem extract, glycerol, caprylic / capric triglyceride, propylene glycol, polysorbate-80, and is prepared by high-speed dispersion processes such as high-speed shearing and high-pressure homogenization, and deformable flexible nano-alcohol bodies are obtained by replacing cholesterol with high-concentration low-chain alcohols (such as propylene glycol and glycerol). The composition has good stability, high transdermal penetration rate, and good transdermal absorbability;
[0059] The experimental results show that the anti-aging composition of the present invention can repair the skin tissue morphology, accelerate the renewal of elastic fibers, promote the production of collagen fibers, and has the effects of anti-aging and firming the skin. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 The amount of anti-wrinkle composition added affects the particle size and Zeta potential of the anti-aging composition;
[0061] Figure 2 The effect of the amount of soybean lecithin added on the particle size and zeta potential of the anti-aging composition;
[0062] Figure 3 It is the effect of the amount of glycerol added on the particle size and zeta potential of the anti-aging composition;
[0063] Figure 4 The effect of the amount of caprylic / capric triglyceride added on the particle size and zeta potential of the anti-aging composition;
[0064] Figure 5 It is the effect of the amount of propylene glycol added on the particle size and zeta potential of the anti-aging composition;
[0065] Figure 6 It is the effect of the amount of polysorbate-80 added on the particle size and zeta potential of the anti-aging composition;
[0066] Figure 7 is the effect of shear time on the particle size and zeta potential of the anti-aging composition;
[0067] Figure 8is the effect of shear speed on the particle size and zeta potential of the anti-aging composition;
[0068] Fig. 9 is the effect of homogenization pressure on the particle size and zeta potential of the anti-aging composition;
[0069] Fig.10 The effect of the number of homogenization times on the particle size and zeta potential of the anti-aging composition;
[0070] Fig.11 It is the interaction between the amount of anti-wrinkle composition added and the amount of soy lecithin added;
[0071] Fig.12 It is the interaction between the amount of anti-wrinkle composition added and the amount of propylene glycol added;
[0072] Fig.13 It is the interaction between the amount of Dendrobium officinale extract added and the amount of propylene glycol added;
[0073] Fig.14 Fluorescence images (200X) obtained by laser confocal photography of the anti-aging compositions of Example 30 and Comparative Example 1;
[0074] Fig.15 are the slice scanning fluorescence images of Example 30 and Comparative Example 1;
[0075] Fig.16 is a bright field superimposed image of the slice scan of Example 30 and Comparative Example 1;
[0076] Fig.17 It is a picture of collagen fibers;
[0077] Fig.18 It is the test result of collagen fiber content;
[0078] Fig.19 Skin tissue morphology pictures;
[0079] Fig. 20 spandex images;
[0080] Fig.21 Elastic fiber content test results;
[0081] Fig. 22 Elastin pictures;
[0082] Fig.23 Elastin content test results. DETAILED DESCRIPTION
[0083] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but the present invention is not limited to the following embodiments.
[0084] The experimental methods described in the following examples are conventional methods unless otherwise specified; the experimental materials and reagents described are commercially available unless otherwise specified.
[0085] The raw materials used in the present invention are shown in Table 1.
[0086] Table 1 Raw materials and their sources
[0087]
[0088] The information of the instruments / equipment used in the present invention is shown in Table 2.
[0089] Table 2 Instrument / equipment information
[0090] Instruments / Equipment Manufacturer Heating magnetic stirrer IKA High speed shear disperser IKA Low temperature ultra-high pressure cell disruptor Guangzhou Juneng Nano Ultrasonic Cleaner GT SONIC High performance liquid chromatography Shimadzu Low temperature high speed centrifuge Sigma Dynamic Light Scattering Malvern
[0091] Examples 1-5
[0092] Table 3 Components and proportions of the anti-aging compositions of Examples 1-5
[0093]
[0094]
[0095] Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition includes 0.0024 wt % of arginine / lysine polypeptide and water To100.
[0096] Embodiment 6-9
[0097] Table 4 Components and proportions of anti-aging compositions of Examples 6-9
[0098]
[0099] Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition includes 0.0024 wt % of arginine / lysine polypeptide and water To100.
[0100] Examples 10-13
[0101] Table 5 Components and proportions of anti-aging compositions of Examples 10-13
[0102]
[0103] Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition includes 0.0024 wt % of arginine / lysine polypeptide and water To100.
[0104] Examples 14-17
[0105] Table 6 Components and proportions of anti-aging compositions of Examples 14-17
[0106]
[0107] Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition includes 0.0024 wt % of arginine / lysine polypeptide and water To100.
[0108] Examples 18-21
[0109] Table 7 Components and proportions of anti-aging compositions of Examples 18-21
[0110]
[0111] Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition includes 0.0024 wt % of arginine / lysine polypeptide and water To100.
[0112] The preparation method of the anti-aging composition of Examples 1-21 is as follows:
[0113] 1) According to the components and proportions of the anti-aging composition shown in Tables 3-7, soybean lecithin, glycerol, caprylic / capric triglyceride and propylene glycol were weighed, and dissolved at 50° C. and 600 rpm / min with magnetic stirring. After the soybean lecithin was fully dissolved, heating was stopped, and palmitoyl pentapeptide-4 was added to obtain an oil phase after dissolution; polysorbate-80, the anti-wrinkle composition and the water extract of Dendrobium officinale stem were weighed and dissolved in water, and ultrasonically dissolved into a uniform system to obtain an aqueous phase;
[0114] 2) Add the oil phase to the water phase for hydration reaction for 20 minutes to obtain a water-oil phase mixture;
[0115] 3) high-speed shearing the water-oil mixture at 9000 rpm for 5 min to obtain a crude alcohol body;
[0116] 4) The crude ethanolate was homogenized under high pressure for 5 times at a pressure of 800 bar to obtain an anti-aging composition.
[0117] Examples 22-30
[0118] Table 8 Process parameters for preparing anti-aging compositions of Examples 22-30
[0119] sample Homogenizing pressure (bar) Homogenization times (n) Shear speed (rpm) Shearing time (min) Embodiment 22 600 3 7000 5 Embodiment 23 600 4 8000 5 Embodiment 24 600 5 9000 5 Embodiment 25 700 3 7000 5 Embodiment 26 700 4 8000 5 Embodiment 27 700 5 9000 5 Embodiment 28 800 3 7000 5 Embodiment 29 800 4 8000 5 Embodiment 30 800 5 9000 5
[0120] The preparation method of the anti-aging composition of Examples 22-30 is as follows:
[0121] 1) Weigh 1.00wt% soybean lecithin, 5.00wt% glycerol, 1.00wt% caprylic / capric triglyceride and 25.00wt% propylene glycol, dissolve them at 50°C and 600rpm with magnetic stirring, stop heating after the soybean lecithin is fully dissolved, add 0.016wt% palmitoyl pentapeptide-4, and obtain an oil phase after dissolution for later use; weigh 0.50wt% polysorbate-80, 50.0wt% anti-wrinkle composition and 0.20wt% Dendrobium officinale stem water extract powder, dissolve them in deionized water, and ultrasonically dissolve them into a uniform system to obtain an aqueous phase for later use;
[0122] 2) Add the oil phase to the water phase for hydration reaction for 20 minutes to obtain a water-oil phase mixture;
[0123] 3) subjecting the water-oil phase mixture to high-speed shearing to obtain a crude alcohol body;
[0124] 4) homogenizing the crude ethanolate under high pressure to obtain an anti-aging composition.
[0125] Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition includes 0.0024 wt % of arginine / lysine polypeptide and water To100.
[0126] The high-speed shear speed, shear time, high-pressure homogenization pressure, and homogenization times of the anti-aging compositions of Examples 22-30 are shown in Table 8.
[0127] Comparative Example 1
[0128] 1.00wt% soy lecithin, 5.00wt% glycerol, 1.00wt% caprylic / capric triglyceride and 25.00wt% propylene glycol were weighed and dissolved at 50°C and 600rpm / min with magnetic stirring. After the soy lecithin was fully dissolved, heating was stopped and 0.016wt% palmitoyl pentapeptide-4 was added to obtain an oil phase after dissolution; 0.50wt% polysorbate-80, 50.0wt% anti-wrinkle composition and 0.20wt% water extract powder of Dendrobium officinale stem were weighed and dissolved in deionized water, and ultrasonically dissolved into a uniform system to obtain an aqueous phase; the oil phase was added to the aqueous phase for hydration reaction for 20min to obtain the anti-aging composition of Comparative Example 1.
[0129] Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition includes 0.0024 wt % of arginine / lysine polypeptide and water To100.
[0130] Test Example 1: Average Particle Size and Zeta Potential Measurement
[0131] The anti-aging composition was diluted 1:1000 times with deionized water and the zeta potential, average particle size and particle size distribution were measured by Malvern dynamic light scattering (DLS) at 25°C. Each sample was measured three times in parallel.
[0132] According to the percentage scoring method, the average particle size is assigned a score using linear interpolation, and different scores are assigned to samples with different average particle sizes. The average particle size is negatively correlated with the skin penetration. The average particle size scoring algorithm is shown in the following formula;
[0133]
[0134] Where: H max ——Maximum average particle size of the sample; H——average particle size of the sample; H min ——Minimum average particle size of the sample.
[0135] 1. Experimental results of average particle size and Zeta potential of anti-aging composition
[0136] Depend on Figure 1 It can be seen that the amount of the anti-wrinkle composition added has a great influence on the average particle size of the anti-aging composition. As the amount of the anti-wrinkle composition added increases, the average particle size shows a trend of first decreasing and then increasing, and the absolute value of the Zeta potential of the anti-aging composition also has this trend. When the amount of the anti-wrinkle composition added is 50.0wt%, the average particle size of the anti-aging composition is the smallest (100.32nm), and the Zeta potential of the anti-aging composition is -39.51mV. Therefore, the amount of the anti-wrinkle composition added is 50wt% as the preferred amount of the anti-aging composition.
[0137] Depend on Figure 2 It can be seen that the addition amount of soybean lecithin has a significant effect on the average particle size of the anti-aging composition, and with the increase of its addition amount, the average particle size shows a trend of first decreasing and then increasing, and the absolute value of the Zeta potential of the anti-aging composition is greater than 40mV, indicating that the samples prepared under the formula have relatively good stability. When the addition amount of soybean lecithin is 1wt%, the average particle size of the anti-aging composition is the smallest (97.38nm) and the PDI is 0.17. Therefore, the addition amount of soybean lecithin is selected as 1wt% as the preferred addition amount of the anti-aging composition.
[0138] Depend on Figure 3It can be seen that the amount of glycerol added has a significant effect on the average particle size of the anti-aging composition, and as the amount of glycerol added increases, the average particle size shows a trend of first decreasing, then increasing, and then continuing to slow down, but the absolute value of the Zeta potential shows a trend of first increasing and then decreasing. In the range of 2.5wt%-5wt% glycerol addition, the average particle size of the anti-aging composition drops to the minimum (101.7nm), the PDI is 0.124, which belongs to a well-dispersed system, and the Zeta potential value of the anti-aging composition is -53.67mV. As the amount of glycerol added further increases, the average particle size of the anti-aging composition increases, and the absolute value of the Zeta potential decreases. Considering the average particle size and the absolute value of the Zeta potential of the anti-aging composition, 5wt% will be selected as the optimal amount of glycerol added.
[0139] Depend on Figure 4 It can be seen that the addition amount of caprylic acid / capric acid triglyceride has a significant effect on the average particle size of the anti-aging composition, and with the increase of its addition amount, the average particle size shows a trend of first decreasing and then increasing, but the absolute value of the Zeta potential shows a phenomenon of first increasing and then decreasing. When the addition amount of caprylic acid / capric acid triglyceride is 0.25wt%-1wt%, with the increase of the addition amount of caprylic acid / capric acid triglyceride, the average particle size of the anti-aging composition decreases, the PDI is less than 0.3, and it belongs to a well-dispersed system. The absolute value of the Zeta potential of the anti-aging composition is increasing. At this time, the average particle size of the alcohol body is 100.7nm, the PDI is 0.202, and the Zeta potential is -48.7mV; when the addition amount of caprylic acid / capric acid triglyceride is 1wt%-1.25wt%, with the increase of the addition amount of caprylic acid / capric acid triglyceride, the average particle size of the anti-aging composition increases significantly, and the absolute value of the Zeta potential of the anti-aging composition also decreases. Taking into account the average particle size of the anti-aging composition and the absolute value of the Zeta potential, 1 wt % is selected as the optimal addition amount of caprylic / capric triglyceride.
[0140] Depend on Figure 5 It can be seen that the amount of propylene glycol added has a significant effect on the average particle size of the anti-aging composition, and as the amount of propylene glycol added increases, the average particle size shows a trend of first decreasing and then increasing, and the absolute value of the Zeta potential shows a trend of first increasing and then decreasing. When the amount of propylene glycol added is 15wt%-25wt%, as the amount of propylene glycol added increases, the average particle size of the anti-aging composition continues to decrease, down to 82.44nm; as the propylene glycol is further increased, the average particle size of the anti-aging composition increases significantly, and the PDI is around 0.2, indicating that the sample systems obtained under each formula are all concentrated and uniformly dispersed systems. Considering that small particle size has better skin permeability, 25wt% will be selected as the optimal addition amount of propylene glycol.
[0141] Depend on Figure 6It can be seen that the amount of polysorbate-80 added has a significant effect on the average particle size of the anti-aging composition, and as the amount of polysorbate-80 added increases, the average particle size shows a trend of first decreasing and then increasing, while the absolute value of the Zeta potential shows a phenomenon of first increasing and then decreasing. In the range of 0.25wt%-1wt% of polysorbate-80 added, as the amount of polysorbate-80 added increases, the average particle size of the anti-aging composition decreases first and then increases, but the overall change is not large. When the amount of polysorbate-80 added is 0.5wt%, the minimum particle size is 83.79nm, the Zeta potential is -33.0mV, and the PDI is 0.201; as the amount of polysorbate-80 added is further added to 1.25wt%, the average particle size of the anti-aging composition significantly increases to 158.67nm. Considering the average particle size and the absolute value of the Zeta potential of the anti-aging composition, 0.5wt% is selected as the preferred amount of polysorbate-80 added.
[0142] Depend on Figure 7-8 It can be seen that with the increase of high-speed shearing time, the average particle size of the anti-aging composition continues to decrease to maintain equilibrium, and the absolute value of the Zeta potential first increases and then maintains little change. When the shearing time is 3 minutes, the average particle size of the prepared alcohol body is 94.1nm. As the shearing time increases, the average particle size of the anti-aging composition does not change much; and the absolute value of the Zeta potential of the anti-aging composition also has this trend. Considering that small particles have better skin permeability and production efficiency, a shearing time of 3 minutes will be selected as the optimal process parameter for the preparation of the anti-aging composition. With the increase of the shearing speed, the shearing speed is 8000rpm, and the average particle size of the anti-aging composition decreases and then remains flat, and the average particle size at this time is 90.83nm. Considering the production cost, a shearing speed of 8000rpm is selected as the optimal process parameter for the preparation of the anti-aging composition.
[0143] Depend on Figure 9-10 It can be seen that with the increase of high-pressure homogenization pressure, the average particle size of the anti-aging composition first decreases and then changes little, and the absolute value of the Zeta potential first increases and then decreases. When the homogenization pressure is 700 bar, the average particle size of the anti-aging composition is 82.5 nm, and the absolute value of the Zeta potential of the anti-aging composition is the largest. Considering that small particle size has better skin permeability and the energy consumption of the instrument, 700 bar will be selected as the optimal process parameter for the preparation of the anti-aging composition. According to the chart data of the influence of different homogenization times on the particle size and Zeta potential of the alcohol body, after homogenization 4 times, the average particle size of the anti-aging composition is 83.4 nm. With the increase of the number of homogenization times, the average particle size of the anti-aging composition does not change much. Considering the production cost, homogenization 4 times is selected as the optimal process parameter for the preparation of the anti-aging composition.
[0144] Test Example 2: Orthogonal Test
[0145] According to the single factor test results, the factor A that increases the average particle size of the anti-aging composition is selected. -1 High pressure homogenization pressure, factor B -1 Homogenization times, factor C -1 The high-speed shear speed was subjected to an orthogonal test with three factors and three waters. The orthogonal experimental design is shown in Table 9.
[0146] Table 9 Optimization factors and levels of process parameters of anti-aging composition
[0147]
[0148] Experimental Example 3: Response Surface Experiment
[0149] According to the results of the single-factor experiment, the materials with larger average particle size of the anti-aging composition were selected as response surface factors, namely, factor A anti-wrinkle composition addition, factor B soy lecithin addition and factor C propylene glycol addition. 17 groups of experiments were designed using Box-Behnken. The test results were based on the particle size score as the response value. The response surface experimental design is shown in Table 10.
[0150] Table 10 Response surface experimental design
[0151]
[0152]
[0153] 2. Orthogonal results and analysis of the preparation method of anti-aging composition
[0154] Table 11 Orthogonal test design and results for optimization of process parameters of anti-aging composition
[0155]
[0156] The experiment was arranged according to the three-factor three-water orthogonal test table, and the results were shown in Table 11. The results showed that the optimal process range of the anti-aging composition was high-pressure homogenization pressure 600-800 bar, homogenization times 3-5 times, and high-speed shear speed 7000-9000 rpm. The influence of each factor on the comprehensive index is: A -1 >B -1 >C -1 , that is, within the range selected by the experimental design, the homogenization pressure has the greatest impact on the comprehensive index, followed by the number of homogenizations, and the shear speed has the least impact. The larger the index value, the better, so the optimal formula for orthogonal is A -1 3B -1 3C -13, that is, the homogenization pressure is 800 bar, the homogenization times are 5 times, and the shear speed is 9000 rpm.
[0157] 3. Response surface design and results of the addition amount of anti-aging composition components
[0158] Table 12 Response surface experimental design and results
[0159]
[0160]
[0161] The results of regression fitting analysis of the data are shown in Table 12. The quadratic regression equation obtained by regression fitting of the three factors of the amount of anti-wrinkle composition added, the amount of soy lecithin added and the amount of propylene glycol added is: Y = 98.87-7.12*A-7.88*B-28.07*C-2.68*A*B-9.55*A*C-0.54*B*C+5.24*A 2 -17.62*B 2 -34.51*C 2 The significance of the coefficient and the strength of the interaction of the combined factors are determined by the P value. The smaller the P value, the more significant it is. From the variance analysis, it can be seen that P<0.0001 shows that the regression model is extremely significant, and the lack of fit term P>0.05 indicates that it is not significant, indicating that the model fits the experimental data well. The determination coefficient R 2 The model was 0.9992, indicating that the model had good fitting and small experimental error. The corrected determination coefficient R2adj of the regression model was 0.9981, indicating that the model could explain 99.81% of the response value changes, and only 0.19% of the changes could not be explained by the model, which once again proved the effectiveness of the model. The model variance analysis showed that the amount of anti-wrinkle composition added (A), the amount of soy lecithin added (B), the amount of propylene glycol added (C), the interaction term between the amount of anti-wrinkle composition added and the amount of soy lecithin added (AB), the interaction term between the amount of anti-wrinkle composition added and the amount of propylene glycol added (AC) and the quadratic terms of each factor had a significant effect on the response value. The order of priority of the factors affecting the comprehensive score of the product was: (C) propylene glycol added > (B) soy lecithin added > anti-wrinkle composition added.
[0162] Table 13 Variance analysis table of regression model
[0163] Regression term sum of squares Degrees of Freedom Mean Square F-number P-value Significance Model 14234.74 9 1581.64 952.5 <0.0001 ** A (Anti-wrinkle composition) 405.41 1 405.41 244.15 <0.0001 ** B(Soybean Lecithin) 496.91 1 496.91 299.25 <0.0001 ** C(propylene glycol) 6304.52 1 6304.52 3796.74 <0.0001 ** AB 28.78 1 28.78 17.33 0.0042 ** AC 364.81 1 364.81 219.7 <0.0001 ** BC 1.17 1 1.17 0.7 0.4297 NS A2 115.73 1 115.73 69.7 <0.0001 ** B2 1307.55 1 1307.55 787.44 <0.0001 ** C2 5014.41 1 5014.41 3019.81 <0.0001 ** Residual 11.62 7 1.66 Lack of Fit 9.39 3 3.13 5.61 0.0645 NS Error term 2.23 4 0.56 / / / Total variation 14246.36 16 / / / / <![CDATA[R 2 ]]> 0.9992 / / / / / <![CDATA[R 2 adj]]> 0.9981 / / / / /
[0164] Note: **The difference is extremely significant, P<0.01; *The difference is significant, P<0.05; NSThe difference is not significant, P>0.05
[0165] The response surface and contour plots of the interaction between the three factors of the amount of anti-wrinkle composition, the amount of soy lecithin added and the amount of propylene glycol added are shown in Figure 2. Figure 11-13As shown. The results show that the optimal formula range of the anti-aging composition is 40wt%-60wt% of the anti-wrinkle composition, 0.75-1.25wt% of soy lecithin, and 20wt%-30wt% of propylene glycol. The response surface plot and contour plot can intuitively reflect the magnitude of the effect of the interaction of the two experimental factors on the response value. If the interaction of the two factors has a greater effect on the response value, the response surface plot will be steeper and the contour lines will be elliptical; if the interaction of the two factors has no significant effect on the response value, the contour lines will be circular. In Figures (a) and (c), the response surface shows a certain degree of convexity and the contour plot is elliptical, indicating that the interaction between the amount of arginine / lysine polypeptide added and the amount of soy lecithin added is significant, and the interaction between the amount of anti-wrinkle composition added and the amount of propylene glycol added is significant.
[0166] The Box-Behnken response surface methodology experiment predicted the optimal formula parameters as follows: the amount of the anti-wrinkle composition added was 50wt%, the amount of soy lecithin added was 1wt%, and the amount of propylene glycol added was 25wt%.
[0167] Test Example 4: Transdermal penetration rate
[0168] 1. Test samples: Example 30, Comparative Example 1
[0169] 2. Test purpose: To evaluate the product's ability to be absorbed through the skin in vitro.
[0170] 3. System and Management
[0171] 1) Experimental animals:
[0172] 2) Name: SD rats (male, 7 weeks old) Grade: SPF grade
[0173] 3) Source: Provided by Zhuhai Baishitong Biotechnology Co., Ltd., Laboratory Animal Production License No.: SCXK (Guangdong) 2016-004
[0174] 4) Reagents
[0175] Table 14 Reagent types
[0176] name brand PBS Solarbio biosharp Normal saline Henan Kelun 4% paraformaldehyde Biosharp
[0177] 5) Instruments and Equipment
[0178] Table 15 Instruments and Equipment
[0179] name brand model Laser confocal microscopy NIKON NIKON Eclipse Ti Digital slide scanner 3D HISTECH Pannoramic DESK Cryostat THERMO CRYOSTAR NX50
[0180] 4. Experimental Procedure
[0181] Dosage method: After euthanasia of SD rats that have passed the quarantine, shave the hair on the back with a shaver, cut the back skin, and rinse it with saline. Remove subcutaneous fat, cut the skin into a diameter / side length of about 2 cm, take 0.3 mL of each prepared marker and drop it on a non-woven fabric of the same size, fix it on the depilated rat skin, and after each sample is exposed for 15 minutes, 30 minutes, 60 minutes, and 120 minutes, absorb the liquid on the skin surface and place it in 4% paraformaldehyde fixative.
[0182] 5. Detection indicators
[0183] 1) Laser confocal microscopy scanning analysis - the sample was FITC-labeled and observed using a single green fluorescence channel with an excitation wavelength of 488 nm and scanning observation at a wavelength above 530 nm.
[0184] 2) Slice scanning: The slices are scanned by a digital scanner to obtain fluorescence scanning images and white light (bright field) scanning images.
[0185] 6. Results Analysis
[0186] Analyze the confocal photos and calculate the fluorescence intensity: fluorescence intensity = fluorescence value / average fluorescence area. The scanning image processing software superimposes the fluorescence image and the bright field scan image. Analyze the fluorescence penetration depth based on the bright field superimposed image.
[0187] 7. Statistics
[0188] All data were expressed as (Mean±SD) and analyzed using SPSS software. If the variance of the measurement data was homogeneous or the variance of the data was homogeneous after transformation, one-way analysis of variance was used. If the variance of the data was still unequal after transformation, the rank sum test was used for statistical analysis. The test level was α = 0.05.
[0189] The fluorescence intensity analysis of the anti-aging composition skin sheet is shown in Table 16, and the fluorescence image obtained by laser confocal photography is shown in Fig.14 .
[0190] Table 16 Fluorescence intensity analysis
[0191]
[0192] Note: * indicates that the data are statistically significantly different from the control sample, p<0.05.
[0193] The experimental results show that at the same exposure time, the fluorescence intensity of the anti-aging composition of Example 30 is greater than that of the comparative example, and is significantly different from the control sample (non-lipidated) at 15 min, 30 min, and 120 min (p<0.05).
[0194] Depend on Fig.15The fluorescence images obtained by laser confocal photography show that under the same exposure time, the fluorescence intensity of the anti-aging composition of Example 30 is greater than that of the comparative example.
[0195] The fluorescence images and bright field images of the cortex were obtained by slice scanning. The fluorescence penetration depth is shown in Table 17 and the fluorescence images are shown in Fig.15 , bright field overlay image see Fig.16 .
[0196] Table 17 Fluorescence penetration depth analysis
[0197]
[0198] Note: * indicates that the data are statistically significantly different from the control sample, p<0.05.
[0199] As shown in the slice scanning fluorescence image and the slice scanning bright field overlay image, there is no significant difference in the penetration depth between the anti-aging composition of Example 30 and the comparative example.
[0200] Examples 31-32
[0201] Table 18 Anti-aging cream formula
[0202]
[0203]
[0204] The preparation process of the anti-aging cream of Example 31 is as follows:
[0205] 1. Premix the xanthan gum and glycerin in group A, add them into deionized water, stir and heat to 85°C, keep warm and stir for 30 minutes until the xanthan gum is completely dispersed and dissolved, and set aside;
[0206] 2. Mix the materials in group B, heat to 85°C to melt the solids, and set aside;
[0207] 3. Quickly add group B into group A and stir to mix evenly. Homogenize for 5 minutes until emulsification is complete;
[0208] 4. Cool down to 40℃, add group C and group D, and stir to mix evenly;
[0209] 5. Pass the membrane and discharge the material.
[0210] The preparation process of the anti-aging cream of Example 32 is as follows:
[0211] 1. Premix the xanthan gum and glycerin in group A, add them into deionized water, stir and heat to 80°C, keep warm and stir for 30 minutes until the xanthan gum is completely dispersed and dissolved, and set aside;
[0212] 2. Mix the materials in group B, heat to 80°C to melt the solids, and set aside;
[0213] 3. Quickly add group B into group A and stir to mix evenly. Homogenize for 3 minutes until emulsification is complete;
[0214] 4. Cool down to 40℃, add group C and group D, and stir to mix evenly;
[0215] 5. Pass the membrane and discharge the material.
[0216] Comparative Example 1-2
[0217] Table 19 Anti-aging cream formula
[0218]
[0219]
[0220] The preparation process of the anti-aging cream of Comparative Example 1-2 is the same as that of Example 31.
[0221] Test Example 5: Firming and Anti-wrinkle Test
[0222] 1. Experimental methods
[0223] 1.1 Test system
[0224] The ex vivo skin tissue used in this test was obtained from Guangdong Boxi Biotechnology Co., Ltd.
[0225] 1.2 Main Reagents
[0226] In vitro skin tissue culture medium (FSK4, Boxi Biotechnology), vitamin C (VC, Sigma), vitamin E (VE, Sigma), paraformaldehyde (Sinopharm Group), and PBS (Boster).
[0227] 1.3 Main Equipment
[0228] CO2 incubator (Thermo, 150i), clean bench (Suzhou Antai, SW-CJ-1F), fluorescence microscope (Leica, DM2500), upright microscope (Olympus, BX53).
[0229] 1.4 Test samples
[0230] Examples 31-32, Comparative Examples 1-2
[0231] 1.5 Test plan
[0232] (1) Prepare the sample working solution according to the test plan table 20.
[0233] Table 20 Sample working solution
[0234]
[0235] (2 Tissue processing: The freshly obtained skin tissue was immersed in 75% alcohol and washed for 30 seconds, and then washed three times with sterile PBS buffer; after that, the skin tissue was cut into small discs with a diameter of 0.6 cm using a disposable sterile skin sampler, with the epidermis facing up and the dermis facing down, and placed in a culture mold. The culture mold was then transferred to a 6-well plate, 3.7 mL of culture medium was added to each well, and cultured in a 37°C, 5% CO2 incubator, with the medium changed every day.
[0236] 3) Administration: After 2 days of in vitro skin tissue culture, UVR irradiation and administration were started with reference to the test groups and corresponding treatment conditions in Table 19; the UVR irradiation dose was UVA (30 J / cm2) and UVB (50 mJ / cm2), and the irradiation was continued for 4 days. After each irradiation, the culture medium was replaced with fresh culture medium, and the drug administration was carried out. The positive control (VC+VE) was administered by submerged administration, and the sample to be tested was administered by surface administration. After 4 days of continuous irradiation, the in vitro skin tissue was cultured for another 3 days, during which no UVR stimulation was performed, and only sample administration was performed.
[0237] 4) Tissue morphology, collagen fiber and elastic fiber detection: After the administration, the skin tissue was fixed with 4% paraformaldehyde, embedded, and sliced for H&E staining, Masson staining, and Victoria blue staining. The slices were collected and photographed using a microscope. Image processing software was used for analysis.
[0238] 5) Data analysis: GraphPad Prism Program software was used for drawing graphs, and t-test was used for statistical analysis between groups. P < 0.05 indicated a significant difference, and P < 0.01 indicated an extremely significant difference.
[0239] 2. Experimental results
[0240] 2.1 Collagen fiber detection results
[0241] Table 21 Collagen fiber content test results
[0242]
[0243] Note: When the t-test method was used for statistical analysis, compared with the BC group, the significance was indicated by #, P-value < 0.05 was indicated by #, and P-value < 0.01 was indicated by ##; compared with the NC group, the significance was indicated by *, P-value < 0.05 was indicated by *, and P-value < 0.01 was indicated by **.
[0244] The test results of collagen fiber content are shown in Table 21 and Figure 17-18 As shown, compared with the BC group, the collagen fiber content of the NC group was significantly decreased, indicating that the stimulation conditions of this experiment were effective; compared with the NC group, the collagen fiber content of the PC group was significantly increased, indicating that the positive control test was effective; compared with the NC group, the collagen fiber content of Examples 31 and 32 was significantly increased.
[0245] 2.2 Tissue morphology test results
[0246] The results of tissue morphology test are as follows Fig.19 As shown, compared with the BC group, the epidermal live cell layer of the NC group became thinner, and the density of fibroblasts in the dermis decreased, indicating that the UVR stimulation conditions were effective; compared with the NC group, the epidermal live cell layer of the PC group was significantly thickened, and the density of fibroblasts in the dermis increased, indicating that the positive control test was effective; compared with the NC group, the epidermal live cell layer of the Example 31 medication group was thickened, and the density of fibroblasts in the dermis of Example 31 increased, indicating that the sample had a certain improvement on tissue morphology.
[0247] 2.3 Elastic fiber test results
[0248] Table 22 Elastic fiber content test results
[0249]
[0250] Note: When the t-test method was used for statistical analysis, compared with the BC group, the significance was indicated by #, P-value < 0.05 was indicated by #, and P-value < 0.01 was indicated by ##; compared with the NC group, the significance was indicated by *, P-value < 0.05 was indicated by *, and P-value < 0.01 was indicated by **.
[0251] The test results of elastic fiber content are shown in Table 22 and Figure 20-21 As shown, compared with the BC group, the elastic fiber content of the NC group was significantly decreased, indicating that the stimulation conditions of this experiment were effective; compared with the NC group, the elastic fiber content of the PC group was significantly increased, indicating that the positive control test was effective; compared with the NC group, the elastic fiber content of Example 31 was significantly increased.
[0252] 2.4 Elastin test results
[0253] Table 23 Elastin content test results
[0254]
[0255] Note: When the t-test method was used for statistical analysis, compared with the BC group, the significance was indicated by #, P-value < 0.05 was indicated by #, and P-value < 0.01 was indicated by ##; compared with the NC group, the significance was indicated by *, P-value < 0.05 was indicated by *, and P-value < 0.01 was indicated by **.
[0256] Compared with the BC group, the elastin content of the NC group decreased significantly, indicating that the stimulation conditions of this test were effective. Compared with the NC group, the elastin content of the PC (VC + VE) group increased significantly, indicating that the positive control test was effective. Compared with the NC group, the elastin content of Example 31 increased significantly.
[0257] Based on Ex vivo skin tissue, an aging model was established by ultraviolet induction. Compared with the NC group, the density of fibroblasts in the dermis of the group treated with the anti-aging cream of Example 31 increased, the tissue morphology was improved to a certain extent, and the collagen fiber content was significantly increased. It is believed that the anti-aging cream of Example 31 achieves anti-wrinkle effect by increasing the total amount of collagen to antagonize the formation of wrinkles caused by collagen loss during skin aging.
[0258] Compared with the NC group, the elastic fiber content and elastin content of the group administered with the anti-aging cream of Example 31 were significantly increased. It is believed that the anti-aging cream of Example 31 antagonizes the decrease in elasticity during skin aging by enhancing elastic fibers and elastin, thereby achieving a firming effect.
Claims
1. An anti-aging composition, characterized in that In terms of weight percentage, the anti-aging composition comprises 30.00wt%-70.00wt% of an anti-wrinkle composition, 0.50wt%-2.50wt% of soybean lecithin, 2.50wt%-12.50wt% glycerol, 0.25wt%-1.25wt% caprylic / capric triglyceride, 15.00wt%-35.00wt% propylene glycol, 0.25wt%-1.25wt% polysorbate-80, 0.01wt%-0.03wt% palmitoyl pentapeptide-4, 0.10wt%-0.20wt% Dendrobium officinale stem extract, water To100; Based on the weight of the anti-wrinkle composition, the anti-wrinkle composition comprises 0.001wt%-0.005wt% arginine / lysine polypeptide, water To100; The anti-aging composition is prepared by a preparation method comprising the following steps: 1) preparing an oil phase and an aqueous phase, wherein the oil phase comprises soybean lecithin, glycerol, caprylic / capric triglyceride, propylene glycol and palmitoyl pentapeptide-4; and the aqueous phase comprises polysorbate-80, an anti-wrinkle composition and a Dendrobium officinale stem extract; 2) adding the oil phase to the water phase for hydration reaction to obtain a water-oil phase mixture; 3) subjecting the water-oil phase mixture to high-speed shearing to obtain a crude alcohol body; 4) The crude alcoholate is subjected to high pressure homogenization to obtain the alcoholate.
2. The anti-aging composition according to claim 1, characterized in that The method for preparing the oil phase in step 1) comprises: weighing soy lecithin, glycerol, caprylic / capric triglyceride and propylene glycol, dissolving them, adding palmitoyl pentapeptide-4, and dissolving them to obtain the oil phase; and / or the method for preparing the water phase comprises: weighing polysorbate-80, the anti-wrinkle composition and the stem extract of Dendrobium officinale, dissolving them in water, and dissolving them to obtain the water phase.
3. The anti-aging composition according to claim 1, characterized in that The hydration reaction time in step 2) is 10-30 min.
4. The anti-aging composition according to claim 1, characterized in that In the step 3), the high-speed shearing speed is 6000-10000 rpm and the high-speed shearing time is 1-5 min.
5. The anti-aging composition according to claim 1, characterized in that In the step 4), the high-pressure homogenization pressure is 600-1000 bar, and the number of high-pressure homogenization times is 3-7 times.
6. The method for preparing the anti-aging composition according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: 1) Weigh 0.50wt%-2.50wt% soybean lecithin, 2.50wt%-12.50wt% glycerol, 0.25wt%-1.25wt% caprylic / capric triglyceride and 15.00wt%-35.00wt% propylene glycol are dissolved, and 0.01wt%-0.03wt% palmitoyl pentapeptide-4 is added and dissolved to obtain an oil phase; 0.25wt%-1.25wt% polysorbate-80, 30.00wt%-70.00wt% anti-wrinkle composition and 0.10wt%-0.20wt% Dendrobium officinale stem extract are weighed and dissolved in water to obtain an aqueous phase; 2) Add the oil phase to the water phase for hydration reaction for 10-30 minutes to obtain a water-oil phase mixture; 3) High-speed shearing the water-oil mixture at 6000-10000 rpm for 1-5 min to obtain a crude alcohol body; 4) The crude alcoholate is homogenized at a pressure of 600-1000 bar for 3-7 times to obtain an alcoholate.
7. Use of the anti-aging composition according to any one of claims 1 to 5 or the anti-aging composition prepared by the preparation method according to claim 6 in the preparation of cosmetics and / or skin care products.
8. The use according to claim 7, characterized in that The anti-aging composition can repair the skin tissue morphology and / or accelerate the renewal of elastic fibers and / or promote the generation of collagen fibers.
9. The use according to claim 7, characterized in that The anti-aging composition can resist aging and / or tighten the skin.
Citation Information
Patent Citations
Anti-aging composition as well as preparation method and application thereof
CN107854355A
Wrinkle-removing and anti-aging composition as well as preparation method and application thereof
CN112641702A